Mode Division Multiplexing Based on Supermodes in Densely Packed Uniform Waveguide Array (DPUWA) - Kaixuan Chen; Liu Liu; Sailing He (IEEE Photonics Journal, 2020)
A multimode bus structure consisting of densely packed uniform waveguide array (DPUWA) with a narrow gap of 150 nm is proposed. A compact and robust mode converter between DPUWA and a conventional wide multimode waveguide is designed with an insertion loss of <; 0.05 dB and crosstalk of <; -20 dB in a wide wavelength range for three TE and three TM modes. Supermodes in the DPUWA can be routed and processed just like the mode in a single-mode waveguide by simply expanding the gap without any mode (de)multiplexer. Based on such ideas, compact DPUWA crossing/bending structures with losses of <; 0.2/0.09 dB and crosstalks of <; -34/-30 dB for three TE modes are achieved.